2017
DOI: 10.1111/ppl.12648
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of a stromule‐overproducing Arabidopsis mutant suggest the role of PARC6 in plastid morphology maintenance in the leaf epidermis

Abstract: Stromules, or stroma-filled tubules, are thin extensions of the plastid envelope membrane that are most frequently observed in undifferentiated or non-mesophyll cells. The formation of stromules is developmentally regulated and responsive to biotic and abiotic stress; however, the physiological roles and molecular mechanisms of the stromule formation remain enigmatic. Accordingly, we attempted to obtain Arabidopsis thaliana mutants with aberrant stromule biogenesis in the leaf epidermis. Here, we characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 67 publications
(139 reference statements)
5
41
0
Order By: Relevance
“…The G62R mutation is located in the TP of PARC6 (Glynn et al, 2009), whereas the W700stop mutation is present in the C-terminal region. Additionally, mutant analysis indicated that the enlarged size and excessive stromule proliferation phenotypes of parc6-5 pavement cell plastids are similar to those of other parc6 alleles, including parc6-1, parc6-3, and parc6-4 (Itoh et al, 2018). Our results also indicated that PARC6 interacts with AtMinD1 (also known as ARC11), another chloroplast division site regulator in mesophyll and pavement cells (Marrison et al, 1999;Colletti et al, 2000;Vitha et al, 2003;Fujiwara et al, 2004;Fujiwara et al, 2008;Fujiwara et al, 2009b;Fujiwara et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…The G62R mutation is located in the TP of PARC6 (Glynn et al, 2009), whereas the W700stop mutation is present in the C-terminal region. Additionally, mutant analysis indicated that the enlarged size and excessive stromule proliferation phenotypes of parc6-5 pavement cell plastids are similar to those of other parc6 alleles, including parc6-1, parc6-3, and parc6-4 (Itoh et al, 2018). Our results also indicated that PARC6 interacts with AtMinD1 (also known as ARC11), another chloroplast division site regulator in mesophyll and pavement cells (Marrison et al, 1999;Colletti et al, 2000;Vitha et al, 2003;Fujiwara et al, 2004;Fujiwara et al, 2008;Fujiwara et al, 2009b;Fujiwara et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…Our results also indicated that PARC6 interacts with AtMinD1 (also known as ARC11), another chloroplast division site regulator in mesophyll and pavement cells (Marrison et al, 1999;Colletti et al, 2000;Vitha et al, 2003;Fujiwara et al, 2004;Fujiwara et al, 2008;Fujiwara et al, 2009b;Fujiwara et al, 2017). However, unlike parc6, arc11 shows fairly modest pavement cell chloroplast phenotypes (Fujiwara et al, 2017;Itoh et al, 2018).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations